Development of modified domino card teaching aids on the subject of earth structure and its development to improve learning outcomes of students in junior high school - Rachel Yesianti Argita; Syubhan Annur; Ellyna Hafizah (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2026)
The limited availability of interactive and effective teaching aids in science education, particularly for abstract topics such as the structure of the Earth and its development, remains a challenge at the junior high school level. Existing learning media often fail to actively engage students and to support optimal conceptual understanding, resulting in low learning outcomes. Although game-based learning media such as domino cards have been shown to enhance student engagement, their systematic development and validation as teaching aids for Earth structure material remain limited. This study aims to develop and evaluate the feasibility of modified domino card teaching aids in terms of validity, practicality, and effectiveness in improving student learning outcomes. The study employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model with a one-group pretest–posttest design. The validity of the teaching aids was assessed by five experts, consisting of three lecturers and two educators. Limited trials involving 10 students were conducted to measure practicality and effectiveness. The results showed that the modified domino card teaching aids achieved a validity score of 0.80 (very valid), a practicality score of 0.92 (very practical), and an average N-gain of 0.91 (high). These findings indicate that the developed teaching aids are valid, practical, and effective for improving junior high school students’ learning outcomes. Abstrak. Keterbatasan alat peraga yang interaktif dan efektif dalam pembelajaran IPA, khususnya pada materi yang bersifat abstrak seperti struktur bumi dan perkembangannya, masih menjadi tantangan di tingkat sekolah menengah pertama. Media pembelajaran yang tersedia umumnya belum mampu melibatkan peserta didik secara aktif serta mendukung pemahaman konsep secara optimal, sehingga berdampak pada rendahnya hasil belajar. Meskipun media pembelajaran berbasis permainan seperti kartu domino terbukti meningkatkan keterlibatan siswa, pengembangannya sebagai alat peraga yang dirancang secara sistematis dan tervalidasi khusus untuk materi struktur bumi masih terbatas. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi kelayakan alat peraga kartu domino modifikasi ditinjau dari aspek validitas, kepraktisan, dan keefektifan dalam meningkatkan hasil belajar peserta didik. Penelitian ini menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation) dengan desain one-group pretest–posttest. Validitas alat peraga dinilai oleh lima validator yang terdiri atas tiga dosen dan dua pendidik. Uji coba terbatas melibatkan 10 peserta didik untuk menilai kepraktisan dan keefektifan. Hasil penelitian menunjukkan bahwa alat peraga kartu domino modifikasi memiliki nilai validitas sebesar 0,80 dengan kategori sangat valid, nilai kepraktisan sebesar 0,92 dengan kategori sangat praktis, serta nilai N-gain rata-rata sebesar 0,91 dengan kategori tinggi. Temuan ini menunjukkan bahwa alat peraga kartu domino modifikasi layak digunakan sebagai media pembelajaran IPA dan efektif dalam meningkatkan hasil belajar peserta didik SMP.